Detecting Genetic Variation of Colonizing Streptococcus agalactiae Genomes in Humans: A Precision Protocol - Zhou, Yan; Zhao, Xue-Chao; Wang, Lin-Qi; Chen, Cheng-Wen; Hsu, Mei-Hua; Liao, Wan-Ting; Deng, Xiao; Yan, Qing; Zhao, Guo-Ping; Chen, Chyi-Liang; Zhang, Liang; Chiu, Cheng-Hsun (Frontiers in Bioinformatics, 2022)
Deciphering genotypic diversity of within-individual pathogens and verifying the evolutionary model can help elucidating resistant genotypes, virulent subpopulations, and the mechanism of opportunistic pathogenicity. However, observed polymorphic mutations (PMs) are rare and difficult to be detected in the ‘dominant-lineage’ model of bacterial infection due to the low-frequency. The four pooled group B streptococcus (GBS) samples were collected from the genital tracts of healthy pregnant women, and the pooled samples and the isogenic controls were genomically sequenced. Using the PMcalling program, we detected the PMs in samples, and especially compared the results between two technical duplicates, GBS-M001T and GBS-M001C. Tested with simulate datasets, the PMcalling program showed high sensitivity especially in low-frequency PMs and reasonable specificity. The genomic sequence data from pooled samples of GBS colonizing carrier pregnant women were analyzed, and few high-frequency PMs and some low-frequency PMs were discovered, indicating a dominant-lineage evolution model. The PMs were mostly nonsynonymous, and enriched in quorum sensing, glycolysis/gluconeogenesis, ATP-binding cassette (ABC) transporters, etc., suggesting antimicrobial or environmental selective pressure. The re-analysis of the published Burkholderia dolosa data showed a diverse-community model, and only a few low-frequency PMs were shared between different individuals. Genes of general control non-repressible 5-related N-acetyltransferases family, major facilitator superfamily (MFS) transporter, and ABC transporter were positive selection candidates. Our findings indicate an unreported nature of the dominant-lineage model of GBS colonization in healthy women, and a formerly not observed mutation pool in colonized microbial community, possibly maintained by selection pressure.